Context matters: athletes’ perception of dopers’ values, actions and vulnerabilities - Veltmaat, Annalena; Dreiskämper, Dennis; Brueckner, Sebastian; Bondarev, Dmitriy; Heyes, Andrew; Barkoukis, Vassilis; Elbe, Anne-Marie; Lazuras, Lambros; De Maria, Alessandra; Zelli, Arnaldo; Petróczi, Andrea (Frontiers in Sports and Active Living, 2023)
Background: Although athletes seem to hold uniform views towards non-dopers, their perception of dopers is more nuanced, reflecting positive and negative attributes. Research also indicates that rarely a single factor can explain doping, but a host of reasons that intertwine. A holistic understanding of how values play a role in decisions in anti-doping and the elements that influence athletes’ doping vulnerability is timely and warranted. Methods: We recruited elite athletes from 13 countries representing 27 sports at a national or international level (N = 60) to participate as part of a larger research project. Data were collected via focus group interviews focusing on values, value priorities and perceptions about the role of values in doping as a phenomenon and in dopers’ actions. Data were analysed using iterative thematic analysis. Results: Three themes were identified: (1) athletes’ personal stance on doping, (2) dopers in the eyes of the anti-doping-compliant athletes, and (3) doping vulnerability is a balance. Athletes in this study strongly opposed doping but showed empathy and understanding toward athletes who doped under certain circumstances. Furthermore, athletes believed that “clean” and “doping” athletes are not always distinguished by the values they hold, leading to the realisation that all athletes can be vulnerable to doping at some point. This vulnerability is a balance between risks and protective factors in a complex interaction between environmental, personal, and situational influences. Each element (e.g., values, environment) can be a motivator or a barrier. Consequently, doping vulnerability is highly idiosyncratic and dynamic. Conclusion: If doping is not due to a lack of moral values but the consequences of combined risk factors that override the guiding function of values, then doping can happen to anyone, “good” athletes included. Developers and facilitators of anti-doping education programmes are advised to embrace this important aspect. The results also contribute to developing the doping vulnerability concept as a balance between risks and protective factors and draw attention to the clean athlete vulnerability, which is rooted in the combination of strategic performance enhancement via non-prohibited means, their exposure to anti-doping requirements and the constant high level of suspicion that surrounds them.